Analysis of Defects and Electrical Characteristics of Variable-Temperature Proton-Irradiated 4H-SiC JBS Diodes - Liansheng Zhao (Electronics, 2022)
The defects and electrical characteristics of 4H-SiC JBS diodes irradiated by 2 MeV protons under irradiation temperatures of 100–400 K were studied. Forward and reverse current–voltage (I–V), capacitance–voltage (C–V), and deep-level transient spectroscopy (DLTS) measurements were performed to study the changes in the characteristics of the device before and after variable-temperature proton irradiation. As the irradiation temperature increased from 100 to 400 K, the on-resistance decreased from 251 to 204 mΩ, and the carrier concentration gradually increased. The reverse current–voltage experiment results showed that the leakage current increased after proton irradiation at each irradiation temperature compared to before irradiation. The DLTS spectra analyses showed that proton irradiation mainly introduced a carbon vacancy related to the Z1/2 center (E0.68 and E0.72), which may have been the main reason for the changes in the forward and reverse electrical characteristics. The intensity of the DLTS spectrum decreased with the increasing irradiation temperature, indicating that the concentration of defects gradually decreased, due to the increase in the radius of the recombination of a vacancy with a related interstitial atom.